Analysis of the EU banking system reactive action through announcement of the prudential regulatory framework revision in the function of preserving financial stability - Klinac, Ivica (Oeconomica Jadertina, 2019)
The establishment of supranational banks regulatory authorities has directly contributed to a better understanding of the behaviour and impact of the banking sector on economic flows comprehensively. Institutional linkage of national regulatory bodies in the context of globalization relations contributes to the desired standardization of data, which are the basis for every valid economic analysis. The market discipline as the backbone of modern regulation reduces especially the banking firm opacity area, while on the other hand the availability of relevant databases expands the horizons of the model approach to banking sector analysis. The dominance of the same sector as a source of external financing on a common European market is the starting point in seeking solutions of emersion from stagnant pressures on economic trends. The dynamism of causative economic relationships imposes the need for ever greater reliability in data sources, hence the representativeness of the sample not only directs an individual research but also determines the cognitive process itself. The analysis of publicly available banking firm data using modern econometric tools is certainly a significant step forward in the attempt to establish a clear and transparent methodological framework for monitoring the reactive activity of the banking sector to the necessary change of regulatory terms in the function of post-crisis launch of the credit cycle. The empirical analysis of the banking sector alignment with new capital requirements will be tested in this paper on a sample of 35 banking groups operating in the EU area for the period from 2000 to 2016, selected by size of assets. The selection of the dynamic panel was performed through panel modelling analysis using Generalized Method of Moments (GMM). The research results have provided evidence that the announcement of the increase in regulatory capital affects the growth of total banking assets, namely there is a significant increase in the share of non-risky assets in bank assets, while on the other hand there is a credit contraction that facilitates the regulatory requirements compliance. Finally, the management structures over the net interest margin as a credit and deposit policy instrument reallocate their own and other resources in the function of preserving the liquidity and solvency of the bank in general.
Keywords: banking system; prudential regulation; capital requirements; dynamic panels